ANALISIS BEBAN KERJA OPERATOR ISOTANK PADA PT ECOGREEN OLEOCHEMICALS BATAM - Candra, Roy; Sri Zetli (LPPM Universitas Putera Batam, 2024)
Working with ISO Tank container loading and unloading equipment, personnel are employed in morning, afternoon, and night shifts, and their tasks are completed around the clock. Operators of ISO Tank Containers put in eight hours a day, and by taking shifts, they may work up to twelve hours. A packed timetable adds to the operator's burden. The aim of this study is to ascertain the physical workload level of PT Ecogreen Oleochemicals Batam isotank operators using the %CVL method, the mental workload level of PT Ecogreen Oleochemicals Batam isotank operators using the NASA-TLX method, and the difference in physical and mental workload on PT Ecogreen Oleochemicals Batam isotank operators. This study employs quantitative methods. The first variable, physical workload, is derived from the %CVL formula, which takes into account pre-work and work pulses. The second variable, mental workload, is derived from the NASA-TLX questionnaire, which includes performance, effort, frustration level, mental demand, physical demand, and temporal demand. The findings demonstrated that, according to the %CVL measurement, ISO Tank operators at PT Ecogreen Oleochemicals Batam most frequently experienced a physical workload with the classification of Improvement required, and that, according to the NASA-TLX measurement, their most common mental workload was in the High category.